Extra-oral comparison of conventional acid-etch technique with self-etch systems in relation to microleakage of fissure sealants in permanent teeth - Marieh Honarmand; Narjes Amiri-Tehranizadeh; Arman Khazaei; Alireza Hosseini Babanari; Fatemeh Khalafinejad (Isfahan University of Medical Sciences, 2013)
Introduction: In recent years use of self-etch primers has been suggested for fissure sealant therapy due to ease of procedural steps. The aim of this in vitro study was to investigate fissure sealant microleakage in permanent teeth with the acid-etch technique, using one-step and two-step self-etch systems.Materials and Methods: A total of 45 sound premolars were selected. Then the occlusal grooves were freshened by the tip of a #1/4 round bur and divided into 3 groups with 15 samples in each group. In the first group after etching by 37% phosphoric acid, Clinpro sealant was applied on the grooves. In the second and third groups, Clearfil SE Bond two-step self-etch and AdheSe One all-in-one one-step self-etch bonding systems were used, respectively. The teeth were subjected to thermocycling for 1000 cycles at 5‒55ºC thermal range. Then the samples were immersed in 0.2% alkaline Fuchsin for 24 hours. After bucco-lingual cross-sectioning, dye penetration under the sealants was evaluated under a stereomicroscope. Data were analyzed by Kruskal‒Wallis and Mann-Whitney tests.Results: The results showed significant differences between the three groups (p value < 0.001). However, there was no significant difference between Clearfil SE Bond and acid-etch groups in microleakage (p value = 0.902). Significantly greater microleakage was observed in the AdheSe One group compared to other groups (p value < 0.0001).Conclusion: According to the results of this study, microleakage of fissure sealants with Clearfil SE Bond two-step self-etch adhesive was comparable to that of conventional etch-and-rinse technique. However, there was more microleakage with AdheSe One one-step self-etch adhesive compared to other two groups. Key words: Bonding, Dental microleakage, Phosphoric acid, Pit and fissure sealants